2006
DOI: 10.1117/1.2364903
|View full text |Cite
|
Sign up to set email alerts
|

Use of lipophilic near-infrared dye in whole-body optical imaging of hematopoietic cell homing

Abstract: Abstract.We develop an optical whole-body imaging technique for monitoring normal and leukemic hematopoietic cell homing in vivo. A recently developed nearinfrared ͑NIR͒ lipophilic carbocyanine dye 1,1Ј-dioctadecyl-3 ,3,3Ј ,3Ј-tetramethylindotricarbocyanine iodide ͑DiR͒ is used to safely and directly label the membranes of human leukemic Pre-B ALL G2 cell lines as well as primary murine lymphocytes and erythrocytes. DiR has absorption and fluorescence maxima at 750 and 782 nm, respectively, which corresponds t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 12 publications
6
75
0
Order By: Relevance
“…There is a need to visualize the migration of immune cells injected into living animals and we achieved this by using a new near-infrared fluorescent dye, DiR (1,1'-dioctadecyl-3,3,3',3'-tetramethyl indotricarbocyanine iodide), although the use of DiR as an in vivo cell tracer is still in its initial experimental stages. Kalchenko et al (6) successfully used DiR to stain human leukemia G2L cells, mouse lymphocytes and rat red blood cells for in vivo tracer experiments. Granot et al (7) also used DiR to mark fibroblast cells, which were then observed targeting to an ovarian cancer tumor some distance away from the injection site.…”
Section: A B Discussionmentioning
confidence: 99%
“…There is a need to visualize the migration of immune cells injected into living animals and we achieved this by using a new near-infrared fluorescent dye, DiR (1,1'-dioctadecyl-3,3,3',3'-tetramethyl indotricarbocyanine iodide), although the use of DiR as an in vivo cell tracer is still in its initial experimental stages. Kalchenko et al (6) successfully used DiR to stain human leukemia G2L cells, mouse lymphocytes and rat red blood cells for in vivo tracer experiments. Granot et al (7) also used DiR to mark fibroblast cells, which were then observed targeting to an ovarian cancer tumor some distance away from the injection site.…”
Section: A B Discussionmentioning
confidence: 99%
“…With new imaging technology at hand, this approach can now be directly translated into in vivo imaging models. DiR has previously been used to label lymphocytes and erythrocytes and monitor the homing of these cells to different organs for up to 96 h after intravenous injection into mice using 2-dimensional reflectance imaging (22). The specificity of homing was verified, and no toxicity was observed in this study.…”
Section: Discussionmentioning
confidence: 81%
“…It has been reported that the two 18 carbon chains of DiR could insert into the liposome membrane, resulting in specific and stable liposome staining, with negligible dye transfer between liposomes and tissue cells. 33 …”
Section: Results and Discussion Preparation Of Sbs Vpg And Sbs Dir Vpgmentioning
confidence: 99%